'Post-truth' schooling and marketized education: explaining the decline in Sweden's school quality. Issue 5 (October 2019) - Henrekson, Magnus; Wennström, Johan
Abstract: The Swedish school system suffers from profound problems with teacher recruitment and retention, knowledge decline, and grade inflation. Absenteeism is high, and psychiatric disorders have risen sharply among Swedish pupils. In this pioneering analysis of the consequences of combining institutionalized social constructivism with an extensive marketization of education, we suggest that these problems are to no small extent a result of an unlikely combination of a postmodern view of truth and knowledge, the ensuing pedagogy of child-centered discovery, and market principles. We show how the stipulated view of truth and knowledge and the design of the system impacts on the incentives for the various agents involved: pupils, parents, teachers, principals, school owners, the municipality, the central government, and, ultimately, the general public. Our study implies that caution is necessary for countries that have a tradition of social-constructivist practices in their education systems and are considering implementing or expanding market-based school reforms.